Causality relationship between electricity consumption and economic activity in Malaysia - Islam, Mohd Aminul (2011)
Although the earlier growth theories such as the “Harrod-Domar” growth model as well as the “Solow-Swan” growth model did not consider energy as an important input in the production function, in recent many energy economists (e.g., Stern, 1993, 1997, 2000; Pokrovski, 2003; Thompson, 2006 etc.) contended that energy is a crucial factor that plays important role in the production of output and hence in the development and growth of the economy. In generating economic activities it is a requisite to have adequate and regular supply of energy resources lacking of which may hamper the development efforts. Adequate power supply may be one of the key energy factors that heavily supports economic growth and the improvement in the quality of life in many rapidly developing countries including Malaysia. Many studies have shown that the energy consumption including power supply has positive correlation with economic growth. Particularly countries with higher per capita GDP tend to have higher per capita energy consumption (e.g., Burney, 1995; Anderson, 1973; Jumbe, 2004; Ferguson et al., 2000; Asafu-Adjaye, 2000). Malaysia has experienced a rapid expansion of the industrial and urbanization development over the last few decades. This has enabled Malaysia to achieve a remarkable success in her pursue of higher economic growth. It is believed that the higher GDP growth has been accompanied by an increased amount of energy use including the consumption of electricity. In per capita terms, the demand for electricity has increased over time in tandem with the growth of the economy. For example, per capita real GDP in 1971 was RM5,219.70 which increased to RM22,173.37 in 2007. Electricity consumption per capita in the respective periods were 311.28 (Kwh) and 3,667.43 (Kwh). The pattern of increasing per capita real GDP and the per capita electricity consumption as depicted in the figure below indicates as a priori, the existence of positive long term relationship between these two factors. This study examines the causal relationship between the per capita electricity consumption and the per capita real GDP in Malaysia over the period 1971-2007. In this bivariate model, the employment rate is incorporated as an intermittent variable to test the relationship within a trivariate causality framework. We utilize bounds testing approach to test the existence of a long run relationship and the vector error correction model to test the direction of causal relationship between the variables under consideration. The test found a unique cointegration between the per capita electricity consumption, employment and the per capita real GDP when the per capita real GDP is used as a dependent variable. The result suggests a long run unidirectional causality from the per capita electricity consumption to the per capita real income and the source of causation is the error correction terms.